Fuel Taxation and Environmental Externalities: Evidence from the World's Largest Environmental Tax Reform - Piero Basaglia; Sophie M. Behr; Moritz A. Drupp (CESifo GmbH, 2025)
We investigate how fuel taxation reduces climate and pollution externalities by evaluating the world's largest environmental tax reform. Using spatially detailed emissions data from more than 1,000 European regions in a synthetic difference-in-differences framework, we evaluate the impact of Germany's 1999 ecological tax reform on transport-related carbon and air pollutant emissions. We document sizable aggregate reductions for all emissions, exceeding 10 percent on average per year relative to synthetic baselines. Using official damage valuations, we estimate avoided external costs of more than exteuro100 billion, two-thirds of which stem from health benefits due to reduced air pollution. Emission reductions and associated monetized benefits are larger in lower-income regions, contrasting with a slightly regressive distribution of fuel costs. These findings underscore the importance of incorporating air quality co-benefits when evaluating the efficiency and distributional effects of fuel and carbon pricing.
Keywords: Q58; H23; I18; R48; 330; environmental policy; externalities; fuel tax; carbon tax; synthetic difference-in-differences; tax elasticity; climate; pollution